PENENTUAN STRUKTUR FORMULA MINERAL LIAT PADA INCEPTISOL DI LAHAN KAMPUS BARU USU KWALA BEKALA - Naomi Eirene Matondang1; Purba Purba; Jamilah Jamilah (Jurnal Agroekoteknologi, 2014)
The Calculations of Formulae Structure of Clay Minerals on Inceptisols at University of NorthSumatera Land Kwala Bekala. The calculation have not been researched in this area. Therefore, aresearch had been conducted survey at USU Land Kwala Bekala Pancur Batu Subdistrict, DeliSerdang Regency (70 meters above sea level) in March-July 2013 by using method of calculation ofsome elements that formation of clay mineral. The results showed that the formulae is (0,025K2O +0,03Na2O + 0,001CaO) (3,27SiO2+ 0,93Al2O3) (1,77Al2O3 + 0,87Fe2O3 + 0,007MnO + 0,03MgO)(3.27SiO2+ 0,93Al2O3) (0,025K2O + 0,03Na2O + 0,001CaO) (4,12OH), this montmoriloniteminerals is not pure because the isomorphous substitution in tetrahedral and octahedral crystalrespectively, be Beidelite mineral.Keywords : Inceptisol, Structural Formulae, Montmorilonite, Beidelite